HUBUNGAN LINGKUNGAN FISIK DAN KARAKTERISTIK KARYAWAN DENGAN PRODUKTIVITAS KERJA DI HOME INDUSTRI KERAJINAN GERABAH - Urianti, Sepriana; Simbolon, Bintang H (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2021)
Pottery craft is a form of home industry that is being developed in Lampung Province. However, several industries show low productivity. This study aims to analyze the relationship between work productivity and physical environmental factors, and worker characteristics. This cross-sectional study was carried out in four pottery-producing home industries involving 35 workers. Data collection was carried out by observation, measurement, and interviews. All data were analyzed using the SPSS 24.0 program. Chi-square test (alpha = 0.05) was applied to determine the relationship of each physical environmental factor and worker characteristics with productivity. The results of the study found that most workers (77.1%) were not productive. Physical environmental factors show a significant relationship with worker productivity, temperature (p = 0.003) and workspace lighting (p = 0.001). Age (p = 0.006) and work experience (p = 0.0001) showed a strong relationship with productivity. Environmental improvement is an urgent need to prevent health problems and increase productivity. On the other hand, it is necessary to increase the knowledge and skills of workers.Â